ANALISIS PENGARUH PERPUTARAN KREDIT TERHADAP TINGKAT LIKUIDITAS KOPERASI KREDIT BUNGA TANJUNG LAMPUNG TENGAH - Jhon Nasyaroeka; Rina milyati Y (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2012)
Cooperative is a business entity consisting of a cooperative or legal entity, with bases itsactivities based on the principle of cooperation as well as people's economic movement, which isbased on the principle of kinship.Credit Cooperative Central Lampung Tanjung Bunga also givecredit to the community or its members.Constraints that often occurs in credit payments are late in paying its debts and uncollectibledebts and this can affect the velocity of money in the cooperative. Therefore please note the level ofhealt cooperatives. The purpose of this study was to determine the effect of rotation on the level ofliquidity credit rate credit cooperatives promontory lampung middle years 2008-2010.Data collection techniques in this study using library research and observation (observation).Data analysis techniques (1) determine the level of liquidity and credit turnover, (2) calculate theregression coefficients by using simple linear regression equation, (3) testing the regressioncoefficients to determine whether the credit cycle really affect the level of liquidity.Based on the above test results are: (1) regression equation Y = 1.004 + - 0.051 X (2) t0 = -0.075, while ta / 2: n-2 = 2.3534, for t0> - ta / 2: n-2 then Ha H0 is accepted and rejected. This showsthat the velocity of the credit has no effect on liquidity. Kuatya cooperative capital and obedience ofthe members to pay these loans play an important role of the cooperative to meet its obligations.